Le rôle de l’agent de probation avec une clientèle à incidence psychiatrique - Leroux, Josette; Larrivée, Gaétan (Criminologie, 1988)
The probation officer in a correctional milieu is confronted more and more by a clientele with various psycho-social pro b -lems, one of them psychiatric. By means of a case study, the authors examined the role of the probation officer in pre-sen-tence evaluation and post-sentence intervention vis-à-vis offenders and referrals to community resourcesThe first objective of the probation officer is to help in some way resolve the social conflict engendered by the offence and keep this in mind when dealing with the offender social services.